Adaptasi Kapasitas Aerobik diikuti oleh Adaptasi Persepsi Pengerahan Tenaga setelah Pelatihan Interval Intensitas Tinggi Selama 6 Minggu - Heru Syarli Lesmana; Padli Padli; Endang Pati Broto; Mikkey Anggara Suganda; Andrew Rinaldi Sinulingga (Indonesian Journal of Physical Education and Sport Science, 2026)
Study purpose: The challenge of monitoring training adaptation has appeared with the demand for a simple, non-exhaustive and efficient approach, since the standardised and sophisticated tools have not been available for athletes in remote area. This study aimed to investigate improvement of the maximum aerobic capacity including heart rate (HR) after 6-week of high-intensity interval training (HIIT) also stimulated the adaptation in rate perceived of exertion (RPE) and furthermore to observe the correlation between these adaptation Materials and methods: Pre-and post-experimental design has been applied to sixteen healthy adults (21±1.1 yr) that completed three times per week cycling HIIT. Before and after intervention, participants underwent two tests in separate days on the cycling ergometer consist of the incremental maximal test to assess maximal heart rate (HRmax) and peak power output (PPO) and the 5-min steady-state exercise (SSE) test with workload 40% and 60% of PPO to assess exercise heart rate (HRexercise), %HRexecise and RPE scale. Results: The HIIT adaptation increased PPO significantly (P<0.001; d=0.41; 302±50.8 to 322±50.9 watt) and decreased HRmax (P=0.001; d=0.43; 188±8.53 to 184±6=7.44 bpm). HRexercise was observed slower in SSE 40% (P=0.005; d=0.55; 127±9.41 to 122±11.9 bpm) and SSE 60% (P=0.001; d=0.63; 153±11.7 to 145±12.6 bpm). The RPE adaptation exhibited a decreasing in SSE 40% (P=0.001; d=1.01; 10±1.25 to 9±0.93) and SSE 60% (P=0.001; d=0.97; 13±0.98 to 12±1.41). The correlation between RPE and HRexercise was established in pre-(r=055, P=0.001) and post-intervention (r=061, P<0.001). Conclusions: Adaptation of HIIT improved the aerobic capacity proved by increase of PPO and decrease HRmax, linked to increase of RPE scale and HRexercise in SSE 40% and SSE 60%. The correlation between RPE and HRexercise was consistently strong pre- and post-intervention. Thus, this finding indicated RPE can be an easy and cost-effective instrument for monitoring intensity and aerobic capacity adaptation.